Prevalence of metachronous contralateral mature ovarian teratoma: A systematic review. Issue 11 (31st July 2021) - Kiely, David; Lewis, Carianne; Gray, Juliet; Hall, Nigel
Abstract: There is increasing recognition that contralateral metachronous tumor may occur following treatment of unilateral mature ovarian teratoma. We aimed to define this risk to guide appropriate surveillance strategies. We undertook a systematic review of three large medical databases (Ovid Medline, Embase, and Cochrane Controlled Trials Register) to April 2020 using a defined search strategy. From 1831 articles retrieved, 23 were included, reporting 1101 girls with unilateral mature ovarian teratomas. The intensity and duration of follow‐up varied between studies, with only five reporting close surveillance. Overall prevalence of metachronous contralateral mature teratoma was 2.1%, with a prevalence per study of 0%–23% (median 0%). Prevalence was higher (7%) among studies with more robust surveillance. These data suggest a small but real risk of metachronous contralateral tumors. Surveillance ultrasonography is proportionate and indicated alongside further prospective data collection to record the natural history and impact of surveillance in greater detail.